IMPLEMENTING COOPERATIVE LEARNING MODEL WITH OPEN ENDED LEARNING APPROACH TO INCREASE STUDENTS’ MATHEMATICS LEARNING OUTCOME AT GRADE III SD NEGERI 110 PEKANBARU - Picka Denko Putra (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
Based on the results of observations conducted at SD N 110 Pekanbaru, the quality of mathematics learning outcomes at grade III was still under KKM. This study aimed to improve the students’ mathematics learning outcomes through cooperative learning models with open ended learning approach. This study utilized classroom action research methods which was conducted in several cycle. Each cycle consisted of four stages including: planning, implementing actions, observing, and reflecting. The data were obtained through observation and tests. The instruments to collect the data were observation sheets and a test. The results showed that implementing cooperative learning models with open ended learning approach improved the students’ learning outcomes in mathematics. It was found that the score increased from 61.84 to 75.26 in the first cycle, and then increased to 81.05 in the second cycle.